2014
DOI: 10.1016/j.neuropsychologia.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control predicted by color vision, and vice versa

Abstract: One of the most important functions of cognitive control is to continuously adapt cognitive processes to changing and often conflicting demands of the environment. Dopamine (DA) has been suggested to play a key role in the signaling and resolution of such response conflict. Given that DA is found in high concentration in the retina, color vision discrimination has been suggested as an index of DA functioning and in particular blue-yellow color vision impairment (CVI) has been used to indicate a central hypodop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…Previous research has suggested CV in the blue-yellow domain is particularly indicative of DA function (Banaschewski et al, 2006;Colzato et al, 2014;Desai et al, 1997;Hulka et al, 2013;Melun et al, 2001;Roessner et al, 2008), although this is not always the case (Barbato, Rinalduzzi, Laurenti, Ruggieri, & Accornero, 1994;Büttner et al, 1995;Shuwairi et al, 2002). However, our results do not indicate a relationship between specific blue-yellow impairment and stop-change performance.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Previous research has suggested CV in the blue-yellow domain is particularly indicative of DA function (Banaschewski et al, 2006;Colzato et al, 2014;Desai et al, 1997;Hulka et al, 2013;Melun et al, 2001;Roessner et al, 2008), although this is not always the case (Barbato, Rinalduzzi, Laurenti, Ruggieri, & Accornero, 1994;Büttner et al, 1995;Shuwairi et al, 2002). However, our results do not indicate a relationship between specific blue-yellow impairment and stop-change performance.…”
Section: Discussioncontrasting
confidence: 83%
“…One study so far has demonstrated CV can predict DA-related cognitive performance. Specifically, CV in healthy young adults predicted individual differences in the cognitive control of response conflict, with better CV predicting reduced response conflict in an auditory Simon task (Colzato, Sellaro, Hulka, Quednow, & Hommel, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that deficits in color vision, particularly blue-yellow impairment, indicate a central hypodopaminergic state (Roy et al, 2003 ). This proposition is consistent with the recent finding that color discrimination predicts cognitive control, with better discrimination being associated with more efficient conflict-resolution in an auditory Simon task (Colzato et al, 2014b ). Given the relation between color vision and DA level, we argue that color vision can predict the effect of TYR supplementation.…”
Section: Indicators and Modulators Of Da Functionsupporting
confidence: 92%
“…For example, individuals with color vision deficiency showed more difficulties in goaldirected activity and in adapting their responses to misleading auditory stimuli while performing their task. 5 Moreover, both adults and children with attention-deficit hyperactivity disorder (ADHD) have repeatedly shown color vision impairments, specifically in the blue spectrum. 6,7 ADHD has been linked with a hypo-dopaminergic state in the retina, thus depressing the perception of dopamine-sensitive ''blue'' cones.…”
mentioning
confidence: 99%